Islamic-Based Farmers’ Group Management in Tobacco Production and Marketing for Members’ Welfare in Senyiur and Pematung Villages - Abdurrahim, Abdurrahim (Pendidikan Agama Islam STIT Palapa Nusantara, 2025)
This study addresses the limited exploration of Islamic-based management practices in the agricultural sector, despite their importance for community welfare and sustainable livelihoods. The research aims to analyze how Islamic principles are applied in farmer group management, particularly in production, marketing strategies, leadership, and conflict resolution, and to examine their contribution to the economic and social welfare of members. This study used a qualitative descriptive approach with a multiple case study design in Senyiur and Pematung villages. Thirty purposively selected participants, including management, active, and ordinary members, were involved. Data were collected through interviews, observations, and document analysis, with triangulation to ensure credibility. Thematic analysis was applied to identify patterns of Islamic values in farmer group management. The findings reveal that Islamic-based farmer group management in Senyiur and Pematung improved members’ welfare through stable income, fair profit-sharing, collective risk management, and stronger spiritual-social bonds. Senyiur prioritized structured coordination, while Pematung emphasized solidarity and ethical distribution. Leadership rooted in moral accountability and participatory decision-making enhanced governance and marketing effectiveness. The integration of Islamic principles—amanah, ‘adl, shura, and ta’awun—not only improved group cohesion and reduced conflicts but also fostered barakah, motivating sustained participation and reinforcing community ties. The study concludes that Islamic-based management plays a crucial role in strengthening farmer organizations by linking ethical values with practical outcomes. Theoretically, it contributes to Islamic economics and group management studies. Practically, it offers insights for policymakers and farmer groups to develop Sharia-compliant models that enhance welfare, sustainability, and resilience.